Émotion et raison : la subjectivité dans les mémoires académiques dans la perspective de la pratique réflexive - Jolanta Rachwalska von Rejchwald (Studia Romanica Posnaniensia, 2022)
The article is devoted to the analysis of academic diploma theses: bachelor’s and master’s, carried out in the course of 1st and 2nd degree Romance Philology between 2005-2017 in the perspective of reflective practice. Based on the assumption of the pre-scientific character of the diploma thesis and the resulting imperative of objectivity, the aim of the article is to examine the traces of subjectivity present in the language of the diploma theses. The subject of interest is both subjectivity expressed in 1 singular person, but above all other, less obvious, more “constructed” forms (e.g. metaphors, expressive use of adjectives), which express the emotional commitment of the author of the work. In conclusion, the analysis of the works shows a conflict of paradigms: the scientific imperative of objectivism with the desire to express emotions aroused by literature, and in this indirect way, also to express one’s self and personality.